2000
DOI: 10.1021/es990757u
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 15N-TNT Residues After an Anaerobic/Aerobic Treatment of Soil/Molasses Mixtures by Solid-State 15N NMR Spectroscopy. 2. Systematic Investigation of Whole Soil and Different Humic Fractions

Abstract: An anaerobic/aerobic composting experiment with 15N-2,4,6-trinitrotoluene (TNT) spiked soil was performed to investigate the fate of the explosive under the applied conditions. For a qualitative description of TNT-residues formed during the composting process, bulk soil and different soil fractions were subjected to solid-state 15N NMR spectroscopy. Major resonance signals could be detected in the chemical shift regions of five-ring heterocyclic nitrogen and in the area of aniline derivatives and primary amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 35 publications
(60 reference statements)
3
42
0
5
Order By: Relevance
“…on May 10, 2018 by guest http://mmbr.asm.org/ subsequent aerated phase eliminated most of the transformation products, possibly by covalent binding to the soil (39,40,134). In tests of the toxic effects of these compounds on human monocytes, leachates of bioremediated soil produced a response similar to that of compost-free of nitroaromatic compounds (41).…”
Section: Applications In Tnt Bioremediationmentioning
confidence: 99%
“…on May 10, 2018 by guest http://mmbr.asm.org/ subsequent aerated phase eliminated most of the transformation products, possibly by covalent binding to the soil (39,40,134). In tests of the toxic effects of these compounds on human monocytes, leachates of bioremediated soil produced a response similar to that of compost-free of nitroaromatic compounds (41).…”
Section: Applications In Tnt Bioremediationmentioning
confidence: 99%
“…There are also many reports of incomplete metabolism resulting in the production of intermediates or dead end by-products that may be reactive with natural organic matter (e.g. humics) (Knicker et al 1999, Bruns-Nagel et al 2000.…”
Section: Biotic -Heterotrophic Bacteriamentioning
confidence: 99%
“…Recently, several laboratory studies and field studies have indicated that energetic compounds, such as explosives, are toxic at relatively low concentrations to a number of organisms including microorganisms (Odlare et al, 2008), plants, invertebrates (Simini et al, 1995), vertebrates and humans (Bruns-Nagel et al, 2000;Beltz et al, 2001). 2,4,6-trinitrotoluene (TNT) and is listed as potential human carcinogen in the USA.…”
Section: Introductionmentioning
confidence: 99%